Analysis of the Influence of Capital Adequacy Ratio, Non-Performing Finance, Financial Deposit Ratio and Inflation on Profitability at PT. Bank Muamalat - Nurjanah, Nurjanah; Juliana (Fakultas Ekonomi dan Bisnis Islam - IAIN Lhokseumawe, 2025)
This study aims to analyze the influence of variables on Bank Muamalat's profitability during 2016-2023 using a quantitative approach. The variables tested included CAR (Capital Adequacy Ratio), NPF (Non-Performing Financing), FDR (Financing-to-Deposit Ratio), and inflation. The results of the study show that the variable that has the most significant influence on profitability is NPF (Non-Performing Financing), which has a significant effect on the bank's profitability. This shows that effective non-performing loan management can directly improve the bank's financial performance. Meanwhile, inflation significantly affects profitability, as rising inflation can reduce consumers' purchasing power and affect banks' performance. On the other hand, the CAR (Capital Adequacy Ratio) does not have a significant effect on profitability, indicating that while maintaining financial stability is important, its impact on profitability is not substantial. The same applies to the FDR (Financing-to-Deposit Ratio), which has no significant effect on profitability. These findings imply that NPF management and inflation monitoring should be the primary focus in efforts to increase the profitability of Islamic banks.